Agreement regarding overcoming hypertension in the Asian Hypertension Society Network 2022 - Hoshide, Satoshi; Yamamoto, Koichi; Katsurada, Kenichi; Yano, Yuichiro; Nishiyama, Akira; Wang, Ji-Guang; Narasingan, S N; Verma, Narsingh; Erwinanto, Erwinanto; Turana, Yuda; Ihm, Sang Hyun; Park, Sungha; et al. (Sprinter Nature, 2023)
The global burden of hypertension has already been acknowledged. The reduction in blood pressure (BP) significantly reduces cardiovascular morbidity and mortality. Half of the world’s population is concentrated in Asia, and this proportion is expected to continue to increase. As the population ages, the number of people suffering from hypertension is also expected to increase. It is critical to address hypertension in Asia. To do so, it is necessary to establish a common direction for the control of hypertension within the Asian region.